Memory and nostalgia in Chow Chin Chuan’s Art / Cheng Jia Wen - Cheng , Jia Wen (2020)
The bicycle as a form of wheeled transport appeared to be the main transportation that was used to carry passengers and goods during the old times, has consistently become the subject matter of Chow Chin Chuan’s artworks over 20 years. Chow is an active artist within the Chinese artist community in Selangor, Kuala Lumpur and Penang area. Currently, there was no well-written research about Chow’s bicycle themed paintings although he has been participated in numerous group art exhibition in oversea countries and also has a total of 8 solo exhibitions in Malaysia as of year 2017. Moreover, currently, there are lack of local research on the Malaysia art. Therefore, this paper can contribute to the documentation of Malaysia art for present and future generations. Apparently, the bicycle in his artworks represents the artist’s childhood memories and reminiscent of his father, however, Chow’s artworks not only just imply his childhood memories, but his paintings that combined the bicycle with street scenes, scene of local lifestyle and other elements may reflect the social and cultural environment of Malaysia. Besides, Chow’s artworks seems to embody the sentimental condition of longing for the past and therefore, nostalgia were used as a conceptual framework to guide the research on Chow’s paintings. A qualitative research will be carried out to study the bicycle as a symbol of his nostalgia and examine how his paintings could acts as a reflection of the Malaya’s cultural past through the theme of nostalgia. The research will also make use of literature review of various publications from the internet, books and newspapers, together with the host of interviews with the artist. The result of this research show that Chow’s bicycle themed paintings is not just reflect his memory and nostalgia, but also convey important ideas about the Peranakan culture and the contribution of traditional trade in Malaysia.